Recording the first wave of the Covid-19 Pandemic in Greece: Expert knowledge, solidarity and effervescence - Καρακωστάκη, Χαριτίνη (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2022)
This paper aims to document the first wave of the Covid-19 pandemic in Greece. It discusses events that shaped the Greek public sphere and contributed to the formation of the collectively lived social experience. It examines the role of epistemic authority in the decision-making process during an emergency, outlines common attitudes and beliefs about the virus and reviews important debates and controversies in the early stages of the pandemic. The description and analysis are based on empirical elements, such as the State’s daily broadcast, which also functioned as a ritual of collective effervescence, as well as important controversies that dominated in the public sphere. Our hypothesis is that citizens were able to respect drastic containment measures because they actually received informed knowledge about the pandemic. In that way, they were convinced beforehand that the strict guidelines were not the mere outcome of an authoritarian government, but primarily the result of evidence-based politics.